2017
DOI: 10.15252/embr.201744100
|View full text |Cite
|
Sign up to set email alerts
|

IFITM 3 requires an amphipathic helix for antiviral activity

Abstract: Interferon-induced transmembrane protein 3 (IFITM3) is a cellular factor that blocks virus fusion with cell membranes. IFITM3 has been suggested to alter membrane curvature and fluidity, though its exact mechanism of action is unclear. Using a bioinformatic approach, we predict IFITM3 secondary structures and identify a highly conserved, short amphipathic helix within a hydrophobic region of IFITM3 previously thought to be a transmembrane domain. Consistent with the known ability of amphipathic helices to alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
162
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(180 citation statements)
references
References 88 publications
12
162
0
Order By: Relevance
“…A number of studies have revealed domains that have important regulatory functions on the antiviral properties of the different IFITM members, influencing their ability to recruit multiple cellular partners and to mediate protection of target cells from viral challenge (19,33,43,(48)(49)(50)(51)(52)(53)(54)(55). However, little is known about domains that specify the negative imprinting properties of IFITMs.…”
mentioning
confidence: 99%
“…A number of studies have revealed domains that have important regulatory functions on the antiviral properties of the different IFITM members, influencing their ability to recruit multiple cellular partners and to mediate protection of target cells from viral challenge (19,33,43,(48)(49)(50)(51)(52)(53)(54)(55). However, little is known about domains that specify the negative imprinting properties of IFITMs.…”
mentioning
confidence: 99%
“…IFITM3 blocks virus fusion with cell membranes via acidic endosome [38,44]. According to the previous reports, the IFITM3 gene is conserved in chimpanzee, Rhesus monkey, mouse, and rat, and 14 organisms have orthologs with human IFITM3 gene (https://www.ncbi.nlm.nih.gov/ gene/10410), indicating a cross protection between species was exist.…”
Section: Discussionmentioning
confidence: 98%
“…IFITM3 is a virus restriction factor which primarily localizes to endosomes and lysosomes [38]. Thus, a suitable vector or strategy is needed to transfer the protein into the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine whether IFITMs are specifically capable of inhibiting fusion mediated individually by Syncytin-1 or -2, we employed a cell-to-cell fusion assay utilizing HEK293T cells, which naturally lack expression of endogenous fusion proteins and endogenous IFITMs, and that we previously validated for studying effects of IFITMs on cell-to-cell fusion mediated by viral fusion proteins (12,17,33). In short, one population of cells was transfected with vector control or Syncytin-1 or -2, while target cells were transfected with individual IFITM expression plasmids or vector control.…”
Section: These Cells Have a Low Baseline Level Of Spontaneous Fusionmentioning
confidence: 99%
“…IFITM constructs cloned into the pCMV-HA vector (Clontech) were described previously (13,31) and myc-FLAG-tagged Syncytin-1 and 2 expression constructs in the pCMV6 vector were purchased from Origene. pFR-Luc and pBD-NFkB (Agilent) were co-transfected with plasmids as indicated in Fig 3A. Cell-to-cell fusion assays were performed as outlined and validated previously (12,17,34). In short, transfections were performed overnight using LipoJet transfection reagent (Signagen).…”
Section: Hek293t Cell Fusion Assaysmentioning
confidence: 99%